Self-Development Program Wearing Children's Pants with Intellectual Barriers - Rozaliana, Dara Ayu; Aprilia, Imas Diana; Homdijah, Oom Sitti (Department of Special Education, 2023)
Self-development using early intervention programs with material wearing shorts. The goal is that children are able to wear shorts independently without the help of others. This study used mixed methods by combining quantitative and qualitative to see the ability of children to wear shorts, The sample of this study was children with intellectual barriers at an early age (under 6 years). Data collection techniques use observation, interviews and documentation. The results of the child's research obtained a significant score, where in treatment 1 the score of children wearing pants was 42.3%, in treatment 2 they got a score of 53.8%, treatment 3 with a score of 65.3%, treatment 4 with an 80.7% score and treatment 5 with an 84.6% score. The results of this study showed an increase in the development of self-development wearing children's pants with intellectual barriers.